2004
DOI: 10.1016/j.indmarman.2003.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Use of the written contract in long-lasting business relationships

Abstract: While contracts are signed in most business dealings, they are seldom used. These contracts are drawn up for different purposes: as a communication tool, to reduce uncertainty, or simply because it is customary. This study investigates how contracts are used in long-lasting business relationships and what factors influence the use of contracts. A number of studies claim that the negotiation process and the relationships developed during that process influence the subsequent use of contracts. In many cases, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 26 publications
3
58
0
Order By: Relevance
“…It has been suggested that long-term and successful business relationships tend to rely less on existing contracts or even exist without formal contracts (Roxenhall and Ghauri 2004).…”
Section: Types Of Business Relationshipsmentioning
confidence: 99%
“…It has been suggested that long-term and successful business relationships tend to rely less on existing contracts or even exist without formal contracts (Roxenhall and Ghauri 2004).…”
Section: Types Of Business Relationshipsmentioning
confidence: 99%
“…Thus it is the desire and ability to take advantage of mistakes, errors and institutional weaknesses when relevant internal or external controls on people's behaviour are absent and one can make gains (Williamson, 1979;Williamson, 2008). Roxenhalla (2004) opine that opportunism is characterized by compromise of integrity; that is, compromising or violating principles and upheld norms in society. It may involve deliberate distortion of information, doing less work than agreed or failing to fulfill formal obligations.…”
Section: Transaction Cost Economics (Tce) and Gmmentioning
confidence: 99%
“…Formal control serves as a tool to address opportunism by its capacity to create mutually and legally agreed range of acceptable behaviours (Li et al, 2010;Liu et al, 2010). Again, contractual agreements do not only specify each party's roles, performance expectations, and dispute resolution mechanisms (Poppo & Zenger, 2002) they also control the actions of the parties to ensure compliance and curb opportunistic behaviours of parties to a particular transaction to drive performance (Macneil 1978;Williamson, 1979;Roxenhalla & Ghauri, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, firms face the problem that they need to anticipate and 'presentiate' (Macneil, 1974) future performance and manifest their agreement in a complete contract (Baker, Gibbons, & Murphy, 2002;Hart & Moore, 1998;Mouzas & Blois, 2013;Schwartz, 1992;Schwartz & Scott, 2015). This problem is evidenced in public procurement, strategic alliances, and R&D projects (Das & Teng, 1999, 2000Reuer & Arino, 2003, 2007Roehrich & Caldwell, 2012;Roehrich, Caldwell, et al, 2014;Roehrich, Lewis, et al, 2014); as well as in continuing business relationships (Harrison, 2004;Ring & Van de Ven, 1992;Roxenhall & Ghauri, 2004).…”
Section: Introductionmentioning
confidence: 99%